Use of Poly (ε-Lysine) Dendrons: A Strategy Targeting Bacterial Quorum Sensing and Biofilm Formation. (11th March 2014) - Issa, Rahaf; Meikle, Steve T.; James, Stuart L.; Cooper, Ian R.
Abstract : Pseudomonas aeruginosa is recognised as a major aetiological agent of nosocomial infections, which are associated with multiple-antibiotic resistance. Among many of its important virulence factors is its ability to form biofilms on the surfaces of implantable medical devices and to produce toxic metabolites, pyocyanin, via an intercellular cell density-dependent signalling system of communication. In this study, poly (ε -lysine) dendrons composed of increasingly branching generations were synthesised, characterised, and examined for their effects on virulence factor production in P. aeruginosa . The results show that these hyperbranched poly (ε -lysine) dendrons, in particular the 3rd generation, can increase the efficacy of a conventional antibiotic, ciprofloxacin, and reduce pyocyanin production, with marginal effects on the rate of bacterial replication, suggesting that the observed effects are not due to dendron toxicity. Furthermore, dendron and ciprofloxacin coadministration was identified as the most effective strategy which highlights the potential of peptide-based dendrons as quorum sensing inhibitors.